Work engagement, high-performance work practices, and job outcomes :an empirical study of millennial frontline employees in the Kenyan hospitality industry - Kibatta, Juliana N. (My University, 2019)
Frontline Employees (FLEs) are considered as the most important link in the service delivery process. They are the initial point of contact between the customer and organization, thus representing a unique set of employees that organizations must actively endeavour to engage and retain. Despite their uniqueness, they are predisposed to numerous work demands and challenges due to the nature of their jobs. Nevertheless, they have the potential to influence the retention of satisfied and loyal customers. As such, organizations must ensure the retention of highly engaged frontline employees, which is vital for organizational success. Further, the ongoing shift in the global workforce characterized by a rapid predominance of younger, millennial, employees in the workplace, has compelled organizations to identify avenues that enhance work engagement levels among this generational cohort. This is largely attributed to millennials’ characterization as being less engaged in their work, relative to preceding generational cohorts. Due to its potential impact on behavioural outcomes in the organization, management practitioners and academics have, increasingly, had to focus on effectively addressing the concept of work engagement among employees. Despite this attention, there is a gap in empirical evidence on the concept of work engagement among millennials, not only in developed, but also developing countries, particularly in Sub-Saharan Africa. This represents a significant problem because a lack of such evidence would constitute a major obstacle for organizations mandated with effectively implementing measures that would otherwise foster work engagement among millennial employees, thereby resulting in less desirable behavioural outcomes and overall organizational performance. This thesis was motivated to address this problem in the context of millennial frontline employees, in the Kenyan hospitality industry. Based on the extant literature, the relationship between a set of determinants (antecedents) and outcomes (consequences) of work engagement, was investigated in this study. An explanatory, predictive research approach was adopted for the study. Specifically, a survey design with a quantitative research strategy was used to empirically examine the relationships between study variables. Using the cross-sectional survey data collected from a sample of full-time frontline employees (n = 405), Exploratory Factor Analysis (EFA) and Confirmatory Factor Analysis (CFA) were conducted to test the validity and reliability of the study’s conceptual model variables. Partial Least Squares - Structural Equation Modeling (PLS-SEM) was used to test the hypothesized relationships between the study’s conceptual model variables. Further, to establish the potential mediating role of work engagement, mediation analysis with bootstrapping procedures were implemented. Subsequently, post-hoc Importance Performance Map Analysis (IPMA) tests, at both the construct and indicator levels, were conducted to further examine the relationships between each of the HPWPs indicators and work engagement, to extend and enrich the results obtained from hypotheses testing. In addition, a test for non-linear quadratic effects was conducted to further investigate the relationship between work engagement and the job outcome variables creative performance, extra-role customer service, and turnover intention, further enriching study findings. Results from the study revealed that training, empowerment, rewards, career opportunities, and job security, are human resource practices (HPWPs) among millennial frontline employees, with rewards being the most important. The results also showed that HPWPs in form of training, empowerment, rewards, career opportunities, and job security, positively influenced work engagement among millennial frontline employees. In addition, the results showed that work engagement is positively associated with extra-role customer service and negatively associated with turnover intention. The findings of this study further showed that work engagement partially mediates the relationship between HPWPs as manifested by training, empowerment, rewards, career opportunities, and job security, and the three job outcome variables. While results of the study have mostly empirically supported prior findings from the extant literature, findings concerning the hypothesized relationship between work engagement and creative performance were contrary to existing empirical evidence. Results from this study showed that work engagement did not have a significant effect on creative performance among millennial frontline employees. Further, results from post-hoc analyses showed that empowerment was a key priority construct for performance improvement by management in enhancing work engagement among millennial frontline employees. Additionally, results showed that work engagement had a curvilinear relationship with turnover intention, while the linear relationships among work engagement and creative performance, and extra-role customer service, were upheld. The findings from the study comprise a significant and meaningful contribution to existing literature on the concept of work engagement by providing substantive empirical insights into its determinants and outcomes in a non-conventional context such as Sub-Saharan Africa. Further, the findings of this study constitute empirical evidence on the important role of work engagement as a significant mediating influence intervening between antecedent HPWPs and consequent job outcomes among frontline employees of the millennial generational cohort in the empirical context of Kenya. Overall, the relevance of effective human resources practices (HPWPs) in enhancing work engagement among frontline employees in the millennial generational cohort, as well as the impact of work engagement on organizationally-valued outcomes, was demonstrated. Additionally, the present study evidences important insights for managers in the hospitality industry who seek to foster engagement among millennial frontline employees. Implications of the study’s findings, limitations, and recommendations of the study are discussed, and provide useful guidance for future research. Keywords: Millennials, Frontline Employees (FLEs), High-Performance Work Practices (HPWPs), Work Engagement (WE), Creative Performance (CRP), Extra-Role Customer Service (ERCS), Turnover Intention (TI), Partial Least Squares - Structural Equation Modeling (PLS-SEM), Importance-Performance Map Analysis (IPMA), Non-Linear (Quadratic) Effects, Human Resource Management (HRM), Hospitality Industry, Hotels, Kenya, Sub-Saharan Africa.
A Thesis Submitted in Fulfilment of the Requirements for the Degree of Doctor of Philosophy (Ph.D.) in Human Resource Management (HRM), October 2019
Keywords: Employees--Kenya; Personnel management; Quality of work life--Kenya